Q Fever (Coxiella burnetii) Knowledge and Attitudes of Australian Cat Breeders and Their Husbandry Practices. (13th September 2016) - Shapiro, A. J.; Norris, J. M.; Bosward, K. L.; Heller, J.
Summary: A Q fever outbreak in a small animal veterinary hospital, associated with a cat caesarean section, initiated a cat seroprevalence study ( n  = 712) that found circulating antibodies to Coxiella burnetii was highest in cattery‐confined breeding cats (9.3%). These findings stimulated interest about potential sources of C. burnetii infection for cats and humans associated with cats. Cat breeders are potentially a group at increased risk of C. burnetii infection, and this study sought to identify potential risk factors. A cross‐sectional online survey was conducted targeting all domestic cat breeders registered with an affiliate member body in Australia in 2015. Responses from 177 cat breeders across Australia were analysed. Forty per cent of responding cat breeders had not heard of Q fever. Raw meat was fed as an integral constituent of the diet by 89% of respondents. Eighty per cent of respondents allowed queens access to the home for parturition, and assistance of queens and resuscitation of kittens at the time of birth were reported by 97% of respondents. Respondents who perceived some level of exposure to Q fever through their breeding activities were three times less likely to perform mouth‐to‐snout resuscitation (OR 0.3 95% CI 0.1–0.9; P  =   0.034) than those who did not perceive a risk of exposure. Similarly, respondents who perceived Q fever as a risk through breeding activities were close to eight times more likely to use personal protective equipment during parturition (OR 7.7 95% CI 1.5–39.9; P  =   0.015) than those who did not. Husbandry practices of cat breeders that may increase the risk of C. burnetii transmission require further targeted investigations to assess the contribution of these risk factors to the acquisition of disease. Concurrent education forums are recommended to inform Australian cat breeders of the aetiopathogenesis of Q fever.